Dynamic streamlined extraction of iridoids, anthocyanins and lipids from haskap berries. (March 2021) - Sainz Martinez, Aitor; Kornpointner, Christoph; Haselmair-Gosch, Christian; Mikulic-Petkovsek, Maja; Schröder, Katharina; Halbwirth, Heidi
Abstract: The European Commission recently authorized the placing of haskap ( Lonicera caerulea L.) berries as a novel food on the EU market. It has been suggested that these berries have several health beneficial properties, due to their considerable content of highly valuable secondary metabolites, such as anthocyanins, phenolic acids, iridoids and fatty acids. Herein, we report a dynamic streamlined extraction process for iridoids and anthocyanins with supercritical carbon dioxide and ethanol as modifier. In particular, we have focused on the iridoids loganic acid and loganin, as well as on different hydroxylation patterns of the anthocyanins. The developed multiple step extraction process leads to initial separation of lipids at low ethanolic concentrations (1 vol%), followed by partial extraction of iridoids at 10 vol% ethanol and ultimately to combined extraction of iridoids and anthocyanins at higher ethanol amounts (>10 vol%). The sequential extraction can be performed in a closed system by automated variation of two innocuous solvents, but uses higher solvent amounts. In comparison to conventional ethanolic extraction, the dynamic streamlined yielded 97% of iridoids and about 7% more anthocyanins. Highlights: Recently authorized novel food haskap contains high iridoid & anthocyanin contents. First supercritical fluid extraction of iridoids and fatty acids from haskap berries. First application of supercritical fluid extraction of loganic acid and loganin. Single dynamic streamlined extraction of fatty acids, iridoids and anthocyanins. Dynamic streamlined process yields 97% of iridoids and 7% more anthocyanins. .